2004
DOI: 10.3354/meps277253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wild fishes on waste exportation from a Mediterranean fish farm

Abstract: This study investigated the role of wild fishes associated with marine farms as potential consumers of organic waste in the water column and sediment. Experiments were carried out at a fish farm in a semi-enclosed bay in the Mediterranean Sea (SE Spain). Sediment traps collected organic waste from net-pens in the water column at different depths during June and July 2001 and benthic caging experiments were carried out on the sediment from October 2000 to January 2001. The experiment showed that about 80% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 33 publications
3
56
1
5
Order By: Relevance
“…For most of the studied aggregating species, it has been demonstrated that they change their diet while resident around farms (FernandezJover et al 2007, 2008) and help to reduce the impact on the benthic system. Thus, wild fish feeding around fish farms reduce the total waste that reaches the environment by 40 to 80% (Vita et al 2004, Felsing et al 2005. Consequently, as wild fish substitute their natural diet by an elevated proportion of food pellets, it was hypothesised that they may present alterations in their FA profiles in a similar way as happens to cultured species.…”
Section: Effects Of Lost Food Pellets On Wild Fish Fa Signaturementioning
confidence: 99%
“…For most of the studied aggregating species, it has been demonstrated that they change their diet while resident around farms (FernandezJover et al 2007, 2008) and help to reduce the impact on the benthic system. Thus, wild fish feeding around fish farms reduce the total waste that reaches the environment by 40 to 80% (Vita et al 2004, Felsing et al 2005. Consequently, as wild fish substitute their natural diet by an elevated proportion of food pellets, it was hypothesised that they may present alterations in their FA profiles in a similar way as happens to cultured species.…”
Section: Effects Of Lost Food Pellets On Wild Fish Fa Signaturementioning
confidence: 99%
“…The Sedimentation trap samples were stored frozen for no longer than two months at -20 ºC and thawed for analysis. After centrifuging at 4°C for 10 min at 1000 g, the overlying water was carefully removed (Vita et al 2004). The settled particles were dried in an oven at 60 ºC to constant weight before being finely ground.…”
Section: Particulate Sedimentation Samplingmentioning
confidence: 99%
“…In parallel, consumption of lost food by wild fish may buffer the environmental impact on the benthos underneath farms (e.g. Lupatsch et al 2003, Vita et al 2004. Therefore, it has been argued that fish harvesting should be avoided in the vicinity of farms , in order to fully benefit from the recycling function of wild fish.…”
Section: Introductionmentioning
confidence: 99%